Autonomic healable waterborne organic-inorganic polyurethane hybrids based on aromatic disulfide moieties - R. H. Aguirresarobe; L. Martin; M. J. Fernandez-Berridi; L. Irusta (eXPRESS Polymer Letters, 2017)
Aromatic disulfide dynamic structures were incorporated as chain extenders in waterborne organic-inorganic polyurethane hybrids in order to provide autonomic healable characteristics. The synthesis was carried out following the acetone process methodology and the influence of the introduction of the healing agents in the polymer dispersion stability was analyzed. After the crosslinking process at room temperature, organic-inorganic hybrid films, which presented autonomic healing characteristics, were obtained. These features were evaluated by means of stress-strain tests and the films showed repetitive healing abilities. Thus, the optimum healing time at room temperature (25 °C) as well as the influence of different parameters in the healing efficiency, such the aromatic disulfide concentration or the physical properties of the polymer matrix were analyzed.